1986
DOI: 10.1021/bi00357a048
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and structural aspects of reconstitution of phosphatidylcholine vesicles by dilution of phosphatidylcholine-sodium cholate mixed micelles

Abstract: Dilution of mixed micellar dispersions of egg phosphatidylcholine (PC) and sodium cholate beyond a critical value results in formation of cholate-containing PC vesicles. The structure of the resultant vesicles and some mechanistic aspects of this process have been investigated by the use of light scattering and nuclear magnetic resonance techniques. The main findings and conclusions are the following: Both the state of aggregation (micellar or vesicular) and the apparent equilibrium size distribution of micell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
90
2
1

Year Published

1988
1988
2005
2005

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(110 citation statements)
references
References 31 publications
17
90
2
1
Order By: Relevance
“…No significant change occur in the turbidity curve of EPC SUV in the region of ReϽ0.23, whilst the turbidity for DMPC SUV increases considerably in the region of 0ϽReϽ0.08, followed by a gradual increase in the region of 0.08ϽReϽ0. 16. The average sizes of DMPC SUV increased from 30 (Reϭ0) to 80-100 nm (Reϭ0.14) accompanied with this turbidity increase, which agreed with the results reported by Malloy and Binford.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…No significant change occur in the turbidity curve of EPC SUV in the region of ReϽ0.23, whilst the turbidity for DMPC SUV increases considerably in the region of 0ϽReϽ0.08, followed by a gradual increase in the region of 0.08ϽReϽ0. 16. The average sizes of DMPC SUV increased from 30 (Reϭ0) to 80-100 nm (Reϭ0.14) accompanied with this turbidity increase, which agreed with the results reported by Malloy and Binford.…”
Section: Resultssupporting
confidence: 90%
“…The molar ratio of Na-chol to PC in the membrane (Re) was employed as a measure of detergent concentration. [15][16][17][18] The Re value was directly measured by equilibrium dialysis method. That is, the vesicle suspension was incubated with an appropriate amount of Na-chol for 1 d using a dialysis cell, which was composed of two compartments and separated by a dialysis membrane.…”
mentioning
confidence: 99%
“…Therefore it was the first method for which a model of vesicle formation was proposed (Lasic, 1982a,b) and for which an experimental search for the mechanism and intermediate structure was performed (Schurtenberger et al, 1984;Almog et al, 1986;Cornell et al, 1986). Later it will be shown that the same mechanism can be applied to the other preparation techniques as well (Lasic, 1987 (Lasic, 1982b) at the (shielded) edges of micelles of the system is proportional to the total circumference (S) of disk-like micelles, since:…”
Section: Mechanism Of Vesicle Formation By Detergent Depletionmentioning
confidence: 99%
“…After a model of vesicle formation by detergent depletion was proposed (Lasic, 1982a,b) several groups tried to confirm this model in which a disk-like micelle is predicted as an intermediate structure in the vesicle formation process (Schurtenberger et al, 1984;Fromherz & Ruppel, 1985;Almog et al, 1986;Cornell et al, 1986) (see the next section). Later this model was also generalized to explain other preparation techniques (Lasic, 1983(Lasic, , 1987 and the mechanisms of the processes involved 1988 in the vesicle formation by all these methods were qualitatively described.…”
Section: Alternative Modelsmentioning
confidence: 99%
See 1 more Smart Citation